2021
DOI: 10.1242/jeb.240960
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic changes in mitochondrial substrate use at critically high temperatures: a comparative study usingDrosophila

Abstract: Ectotherm thermal tolerance is critical to species distribution, but at present the physiological underpinnings of heat tolerance remain poorly understood. Mitochondrial function is perturbed at critically high temperatures in some ectotherms, including insects, suggesting that heat tolerance of these animals is linked to failure of oxidative phosphorylation (OXPHOS) and/or ATP production. To test this hypothesis we measured mitochondrial oxygen consumption rates in six Drosophila species with different heat t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 86 publications
(99 reference statements)
6
40
0
Order By: Relevance
“…Therefore, mitochondrial thermal sensitivity has been put forward to tentatively explain organismal failure at high temperatures and is believed to be paramount for thermal adaptation of several organisms ( Fangue et al, 2009 ; Iftikar et al, 2014 ; Chung et al, 2018 ; Harada et al, 2019 ; Pichaud et al, 2019 ; Hraoui et al, 2020 ; Hraoui et al, 2021 ). However, the study of insects has often been overlooked mainly due to technical reasons which resulted in a gap of knowledge concerning mitochondrial functions and the implication of mitochondrial adaptation in insects at high temperature [but see ( Davison and Bowler, 1971 ; Kashmerry and Bowler, 1977 ; Chamberlin, 2004 ; Pichaud et al, 2010 ; Pichaud et al, 2011 ; Pichaud et al, 2012 ; Pichaud et al, 2013 ; Jørgensen et al, 2021 )]. The population structure and geographic distribution of insects are thus linked to the plasticity of mitochondria and their capacity to buffer daily temperature fluctuations encountered during summer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, mitochondrial thermal sensitivity has been put forward to tentatively explain organismal failure at high temperatures and is believed to be paramount for thermal adaptation of several organisms ( Fangue et al, 2009 ; Iftikar et al, 2014 ; Chung et al, 2018 ; Harada et al, 2019 ; Pichaud et al, 2019 ; Hraoui et al, 2020 ; Hraoui et al, 2021 ). However, the study of insects has often been overlooked mainly due to technical reasons which resulted in a gap of knowledge concerning mitochondrial functions and the implication of mitochondrial adaptation in insects at high temperature [but see ( Davison and Bowler, 1971 ; Kashmerry and Bowler, 1977 ; Chamberlin, 2004 ; Pichaud et al, 2010 ; Pichaud et al, 2011 ; Pichaud et al, 2012 ; Pichaud et al, 2013 ; Jørgensen et al, 2021 )]. The population structure and geographic distribution of insects are thus linked to the plasticity of mitochondria and their capacity to buffer daily temperature fluctuations encountered during summer.…”
Section: Introductionmentioning
confidence: 99%
“…Although mitochondria have been suggested as a putative site of dysfunction resulting in organismal failure at high temperature, no specific mechanism has been identified so far due to their complexity and their involvement in a wide range of metabolic and signalling processes. In a recent study using a comparative model of six different Drosophila species with different thermal tolerance, we showed that heat tolerance (CT max ) was correlated with failure of mitochondrial oxygen consumption at the level of complex I and increased utilization of alternative oxidative substrates ( Jørgensen et al, 2021 ). Specifically, the mitochondrial oxygen consumption supported by complex I substrates was drastically reduced at temperatures near CT max of the specific species, and glycerol-3-phosphate (G3P) oxidation by the mitochondrial glycerol-3-phosphate dehydrogenase (mtG3PDH) was augmented ( Jørgensen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the mean summer temperatures in Barcelona are 5–8°C greater than Oregon, imposing greater metabolic demands on BAR mitochondria (as the Q 10 suggests a doubling in metabolic rate for every 10°C rise in temperature). While the Oregon strain was collected in 1925, hence has had nearly a century to adapt to lab conditions, differences in heat tolerance at the species level can persist for decades in the lab, and correspond to differences in complex I and substrate use ( Jørgensen et al, 2019 , 2021 ). It is possible that BAR flies could have a respiratory architecture adapted to higher temperatures.…”
Section: Discussionmentioning
confidence: 99%